Modelado compacto - Pérez López, Esmeralda (Universidad Michoacana de San Nicolás de Hidalgo, 2016)
In this work we present a model of objects compact statics and spherically symmetric in hydrostatic equilibrium, we studied the case of object electrically neutral. This is applicable for stars with reason of compactness GM c2R < 4 9. We suppose that he fluid is described by subject that presents pressures anisotropic, with a pressures radial described by an equation of state of the kind Chaplyging. The density and the pressures are functions monotones decreasing while that velocity of sound are functions monotones creasing positive and minors what that velocity of that light, that is to say, satisfies all that terms required for to represent a solution physically acceptable. The solution presents a region of stability near from the center and is unstable at the border for speeds of one of the settings for completeness of our work we apply the solution to the case of the stars SMCX-1 that has mass SMCX-1 (1.29 0.05)Mo y radio (1.9027 0.073) Km.

En este trabajo presentamos un modelo de objetos compactos estáticos y esféricamente simétricos en equilibrio hidrostático, se estudió el caso de objetos eléctricamente neutros. Este es aplicable para estrellas con razón de compacidad GM c2R < 4 9 suponemos que el fluido es descrito por materia que presenta presiones anisotrópicas, con una presión radial descrita por una ecuación de estado tipo Chaplyging. La densidad y las presiones son funciones regulares monótonas decrecientes, mientras que las velocidades del sonido son funciones monótonas crecientes positivas y menores que la velocidad de la luz, es decir, satisface todas las condiciones requeridas para que este represente una solución físicamente aceptable. La solución presenta una región de estabilidad cerca del centro y es inestable en la frontera para valores de uno de los parámetros, por completitud de nuestro trabajo aplicamos la solución al caso de la estrella SMCX-1 que tiene masa (1.29 0.05) Mo y radio (1.9027 0.073) Km.
Facultad de Ciencias Físico Matemáticas. Maestría en Ciencias en Ingeniería Física
Keywords: info:eu-repo/classification/cti/1; FISMAT-M-2016-1843; Compacto; Soluciones exactas; Fluido anisotrópico; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3288